Pengaruh Pembelajaran Kooperatif Tipe Think Talk Write terhadap Kemampuan Representasi Matematis Siswa - Okta Zarina; Rini Asnawati (Limacon: Journal of Mathematics Education, 2019)
This experimental research aimed to find out the effect of cooperative learning models type think talk write towards student’s mathematical representation skill. The population in this research was all students of grade 7th of SMPN 1 Lumbok Seminung in the academic year 2018/2019 as many as 81 students, that distributed into three classes. The sample of this research was students of class VII A consist of 27 students and VII B consist of 27 students who were selected by cluster random sampling. The design used was the randomized pretest-posttest control group design. Research data were obtained through an essay test on the comparison. Analysis of this research data used the ???? test. Based on the results of this research and discussion, it concluded that cooperative learning models type think talk write was effect towards students’ mathematical representation skills.